Hydrophobic-barrier-assisted formation of vertically layered capacitive electrodes within a single sheet of paper. Issue 48 (6th December 2021) - Oh, In Hyeok; Lee, Sung Min; Kim, Yeon Woo; Choi, Seyoung; Nam, Inho; Chang, Suk Tai
Abstract : Vertically layered capacitive electrodes within a single sheet of paper are realized by using the hydrophobic barrier in the paper. Abstract : Flexible energy storage devices are of significant interest for wearable device applications. In this regard, paper, which is thin, light, flexible, and highly porous, has emerged as a next-generation energy-storage material. Here, we introduce a facile technology for fabricating a supercapacitor based on a single sheet of paper, in which the electrodes are vertically separated by the patterning of hydrophobic barriers. The positive and negative electrodes can be simultaneously sectionalized as active layers and current collectors in a single-layer porous paper supercapacitor, such that the gel electrolyte infiltrates the device without any additional assembly. The solid-state supercapacitor with vertically layered electrodes exhibits a large areal capacitance of 560.2 mF cm −2 at 0.2 mA cm −2 and stable flexibility and foldability. The maximum power and energy densities were 1.597 mW cm −2 and 28.74 μW h cm −2, respectively, which highly exceed those of previously reported multi-sheet paper-based supercapacitors.